Development of Prevascularized Synthetic Block Graft for Maxillofacial Reconstruction - Borvornwut Buranawat; Abeer Shaalan; Devy F. Garna; Lucy Di Silvio (Journal of Functional Biomaterials)
Cranio-maxillofacial bone reconstruction, especially for large defects, remains challenging. Synthetic biomimetic materials are emerging as alternatives to autogenous grafts. Tissue engineering aims to create natural tissue-mimicking materials, with calcium phosphate-based scaffolds showing promise for bone regeneration applications. This study developed a porous calcium metaphosphate (CMP) scaffold with physicochemical properties mimicking natural bone, aiming to create a prevascularized synthetic bone graft. The scaffold, fabricated using sintered monocalcium phosphate with poly (vinyl alcohol) as a porogen, exhibited pore sizes ranging from 0 to 400 μm, with the highest frequency between 80 and 100 μm. The co-culture of endothelial cells (ECs) with human alveolar osteoblasts (aHOBs) on the scaffold led to the formation of tube-like structures and intrinsic VEGF release, reaching 10,455.6 pg/mL This level approached the optimal dose for vascular formation. Conversely, the co-culture with mesenchymal stem cells did not yield similar results. Combining ECs and aHOBs in the CMP scaffold offers a promising approach to developing prevascularized grafts for cranio-maxillofacial reconstruction. This innovative strategy can potentially enhance vascularization in large tissue-engineered constructs, addressing a critical limitation in current bone regeneration techniques. The prevascularized synthetic bone graft developed in this study could significantly improve the success rate of maxillofacial reconstructions, offering a viable alternative to autogenous grafts.